Alexander the Great rocks the world - Shecter, Vicky Alvear, 1961- (Darby Creek Pub., 2006)
Sixteen-year-old Alexander was left in charge of Macedon when his father, the king, went on a business trip. When a barbarian tribe attacked Macedon, Alexander led the army against them, and won! By 18, Alexander was named a general of the army; at 20 he ruled all of Ancient Greece; at 25 he had conquered most of ancient Persia. By 32, he was really King of the World!